Certification of the Warehouse in rum factory - González Cabrera, Ernesto; Cespón Castro, Roberto; Coello Machado, Norge Isaías; Glistau, Elke (My University, 2021)
Today's business world is becoming increasingly complex and unpredictable for companies. The accelerated development of science and technology, together with the globalization of the market, makes organizations face the need to find solutions that ensure their position in the market, lead to optimizing processes and make them more competitive. An important aspect in this regard is the certification of the entire process, including the warehouse areas. In the research, an extensive review of the current literature was carried out, especially the current resolutions, which allowed us to incorporate elements of logistics 4.0 and human-machine interaction. A procedure is developed that allows self-evaluation according to the level of certification that is chosen. Quality management tools are used, the application increases in complexity as excellence is sought in the storage of finished products. The case study is carried out as a way to improve the current certification level of the finished products warehouse at the Ron Cubay factory.
Keywords: Certification; Warehouse; Quality Management; Logistics 4.0